2007
DOI: 10.1093/jac/dkl497
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral activity of pegylated interferon alfa-2a in patients co-infected with HIV/hepatitis C virus

Abstract: A significant early anti-HIV activity of PEG-IFN alfa-2a was observed. Such an effect warrants further clinical evaluation in the management of co-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…S2 in the supplemental material). This effect is consistent with previous IFN-␣/riba and IFN-␣ monotherapy studies (4,5,7,8). Seven of 15 individuals were included in analyses of PBMC gene expression, and the remaining eight individuals were included in analyses of CD4 ϩ T cell gene expression.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…S2 in the supplemental material). This effect is consistent with previous IFN-␣/riba and IFN-␣ monotherapy studies (4,5,7,8). Seven of 15 individuals were included in analyses of PBMC gene expression, and the remaining eight individuals were included in analyses of CD4 ϩ T cell gene expression.…”
supporting
confidence: 78%
“…Induction of IFN-␣ expression is a critical first step in the defense against a range of viral infections (1,2). The antiretroviral activity of IFN-␣ was demonstrated in vitro soon after the discovery of HIV-1 (3), and several studies have reported that exogenous IFN-␣ treatment potently suppresses HIV-1 in vivo (4)(5)(6)(7)(8). Moreover, IFN-␣ therapy was recently associated with significant reduction in the size of the HIV-1 latent reservoir (9), suggesting that interferon-associated pathways may be exploited to achieve HIV-1 eradication.…”
mentioning
confidence: 99%
“…The antiretroviral activity of the IFN-α cytokine was demonstrated in vitro almost immediately after the discovery of HIV-1, and includes inhibition of HIV-1 reverse transcription, viral assembly, and virion release (26). IFN-α has been reported to suppress HIV-1 viremia in chronically infected individuals (27)(28)(29), and is known to induce APOBEC3 and BST-2 expression in a number of tissues and cell types in vitro (7,(30)(31)(32). However, to date, no data describe the effects of exogenous IFN-α treatment on the expression of these restriction factors in vivo, and the relevance of these factors to virologic control in chronically infected individuals is unknown.…”
mentioning
confidence: 99%
“…Induction of interferon-α (IFN-α) expression is a critical first step in the defense against a range of viral pathogens [1] , [2] . Several studies have demonstrated that IFN-α treatment potently suppresses HIV-1 viremia in chronically infected individuals [3] – [6] . A provocative recent report demonstrated that IFN-α treatment results in sustained viral suppression in the absence of antiretroviral therapy (ART) and significant reduction in the size of the HIV-1 reservoir in chronically-infected individuals [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%